2012
DOI: 10.1111/j.1745-9125.2011.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Transferred Juveniles in the Era of Sentencing Guidelines: Examining Judicial Departures for Juvenile Offenders in Adult Criminal Court*

Abstract: This study contributes to contemporary research on the punishment of juvenile offenders in adult court by analyzing the use of guidelines departures for transferred juveniles in two states, one with presumptive sentencing guidelines (Pennsylvania) and one with voluntary guidelines (Maryland). Propensity score matching is first used to create more comparable samples of juvenile and young adult offenders, and then Tobit regressions are employed to estimate the effect of juvenile status on the likelihood and leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 71 publications
2
51
0
Order By: Relevance
“…The outcome of interest for this study is whether an offender received a judicial downward departure and as a result was sentenced below the guideline range. Following the approach advocated by Johnson and Kurlychek (2012; see also Bushway and Piehl, 2007), our dependent variable encompasses both the likelihood of a judicial downward departure did not produce results significantly different from those presented in this article. Specifically, this model produced an effect size of 2.45 (standard error = 0.47) in the final Tobit model.…”
Section: Dependent and Independent Variables And The Analytic Approachmentioning
confidence: 57%
See 3 more Smart Citations
“…The outcome of interest for this study is whether an offender received a judicial downward departure and as a result was sentenced below the guideline range. Following the approach advocated by Johnson and Kurlychek (2012; see also Bushway and Piehl, 2007), our dependent variable encompasses both the likelihood of a judicial downward departure did not produce results significantly different from those presented in this article. Specifically, this model produced an effect size of 2.45 (standard error = 0.47) in the final Tobit model.…”
Section: Dependent and Independent Variables And The Analytic Approachmentioning
confidence: 57%
“…Following the approach advocated by Johnson and Kurlychek (; see also Bushway and Piehl, ), our dependent variable encompasses both the likelihood of a judicial downward departure and the magnitude of the sentence discount for receiving this type of departure, which is measured by the number of months between the guideline minimum sentence for that offense and an offender's actual sentence received . We analyze this variable using Tobit regression (Tobin, ), which Johnson and Kurlychek () argued more accurately models the departure decision as it accounts for the dependency between the outcomes measured by using a latent variable that incorporates both the likelihood of a departure and its magnitude. This approach is similar to the method used in research on incarceration decisions under sentencing guideline systems (Bushway and Piehl, ; Kurlychek and Johnson, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, prior literature has suggested that the age of the defendant may influence case processing. Specific to the focal concerns perspective, age has been found to exhibit an effect on sentencing decisions, often with the effect being curvilinear (see B. D. Johnson & Kurlychek, 2012;Steffensmeier et al, 1998). To control for this influence, both the defendant's age (ranging 17-82) and the quadratic age term were included in the analyses.…”
Section: Independent Variablesmentioning
confidence: 99%